HUBUNGAN TINGKAT PENGETAHUAN DAN STATUS EKONOMI DENGAN DUKUNGAN KELUARGA PADA PASIEN SKIZOFRENIA DIWILAYAH KERJA PUSKESMAS MONGOLATO - Firmawati Firmawati; Fitriyah Handayani (-, 2021)
Family support is very important in fostering a healthy life. The aim of this research identifying the “The Relationship Level Of Knowledge And Status Economy With The Family Support In Patients With Schizophrenia”. Descriptive quantitative research design form comparative with the sample of 33 respondents. Instrument knowledge level, status economy with the family support by using questioner. The result showed no correlation with the level of knowledge with family support (p=0,001;α=0,05) and there is a correlation with the support of family economic status (p=0,001;α=0,05) in caring for family members of patients with schizophrenia in Puskesmas Mongolato. The research recommends the importance of mental health education programs to families who care for pasients with a history of schizophrenia.